Drought monitoring using multi-time-scale Standardized Precipitation Index - K, PRAJAPATI V; M, KHANNA; M, SINGH; R, KAUR; N, SAHOO R; K, SINGH D; P, DATTA S (The Indian Journal of Agricultural Sciences, 2021)
Drought is a natural hazard that affects almost all regions. In recent years, it has become more intense and frequentcausing adverse impacts on the socio-economic conditions of the country. The primary cause of drought developmentis the deficiency in precipitation impacting crop production during kharif with a follow-up effect also in crops grownduring rabi. The present study was carried out over one of the most drought-prone regions of India, i.e. Marathwadaregion, Maharashtra to characterize meteorological drought through the Standardized Precipitation Index (SPI) duringboth kharif and rabi crop growing seasons. SPI was computed at different time scales (1, 3, 6, 9 and 12-month) usingin-situ precipitation data for 35 years (1980-2014). Drought area observed by multi-time-scale SPI was correlated withdrought declared by the Government and foodgrain production for 15 years (2000–14). It was observed that none ofthe time scales of SPI had a significant correlation with declared drought. However, correlation analysis of multiscaleSPI with foodgrain production showed that 3-month SPI had a significant correlation (r= -0.72) during kharif, while alow correlation was observed between multiscale SPI and foodgrain production for rabi season. Therefore, informationobserved by SPI would be useful if it could be combined with other biophysical conditions and drought indices toincrease its accuracy and reliability for effective drought characterization and monitoring.